2020
DOI: 10.3390/met10070866
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Based Catalysts in the Water Gas Shift Reaction: Recent Advances

Abstract: The water gas shift (WGS) is an equilibrium exothermic reaction, whose corresponding industrial process is normally carried out in two adiabatic stages, to overcome the thermodynamic and kinetic limitations. The high temperature stage makes use of iron/chromium-based catalysts, while the low temperature stage employs copper/zinc-based catalysts. Nevertheless, both these systems have several problems, mainly dealing with safety issues and process efficiency. Accordingly, in the last decade abundant rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 206 publications
1
14
0
2
Order By: Relevance
“…The analysis shows an increase in metal loading (platinum) from 0.5 to 2 wt.% has led to an increase in the value of DoD, however, the further increase has led to a decrease in the degree of dehydrogenation, as shown for 5 wt.% catalyst. This is in agreement with the study by Palma et al [43], i.e., for the metal loading of 2 wt. %, there is a fine dispersion on the base surface with the least agglomeration, while the increase in metal loading from 2 to 5 wt.% has led to a comparative increase in the agglomeration, reduced dispersion, reduced metallic surface area, and reduced number of reducible species, thereby leading to reduced catalytic activity.…”
Section: Resultssupporting
confidence: 94%
“…The analysis shows an increase in metal loading (platinum) from 0.5 to 2 wt.% has led to an increase in the value of DoD, however, the further increase has led to a decrease in the degree of dehydrogenation, as shown for 5 wt.% catalyst. This is in agreement with the study by Palma et al [43], i.e., for the metal loading of 2 wt. %, there is a fine dispersion on the base surface with the least agglomeration, while the increase in metal loading from 2 to 5 wt.% has led to a comparative increase in the agglomeration, reduced dispersion, reduced metallic surface area, and reduced number of reducible species, thereby leading to reduced catalytic activity.…”
Section: Resultssupporting
confidence: 94%
“…In addition to carbon monoxide and hydrogen, in the gas stream at the outlet of the reformer, unreacted methane and carbon dioxide are also present, therefore, further treatment/purification steps are necessary for obtaining pure hydrogen. In particular, one [15] or two stages of CO-water gas shift [16,17] followed by selective methanation [18], preferential oxidation [19] or a treatment with permselective membranes [20]. Although noble metal-based catalysts provide high activity and good stability, the high cost and the limited availability of the noble metals prevent their use, so Ni/Al 2 O 3 is the most used commercial catalyst for MSR [21].…”
Section: Methane Steam Reformingmentioning
confidence: 99%
“…In solid oxide electrolysis cells (SOEC), a solid oxide or ceramic is used as electrolyte; at the cathode side hydrogen is produced from water (17), while the oxygen ions generated, across the electrolyte, reach the anode (16) where they are oxidized to produce oxygen: The solid oxide electrolysis cells typically operate in the temperature range 500-900 • C [177], which provides a crucial benefit over proton exchange membrane (PEM) and alkaline exchange membrane (AEM) electrolyzers, which operate at a maximum of 100 • C. Unfortunately, the degradation of SOEC is the major limitation to the commercial viability, the aggressive humid condition in the air electrode side, is still a concern to the stability of electrolysis cells [178]. Typically, Ni/yttria-stabilized zirconia (Ni/YSZ) electrodes are used [179], however agglomeration of Ni nanoparticles, low water vapor transmission efficiency and poor durability are serious issues [180].…”
Section: Solid Oxide Electrolysis Cellsmentioning
confidence: 99%
“…Interestingly, different mechanisms have been reported for nearly identical formulations in some cases (e.g., Pt supported on ceria-zirconia mixed oxides) [11,12]. In a recent review, Palma et al summarize the mechanisms proposed for many Pt-based catalysts in the recent literature [13]. In the review, the authors note that an associative mechanism was reported for all the alkali promoted Pt-based catalyst formulations investigated.…”
Section: Introductionmentioning
confidence: 99%